2007
DOI: 10.1590/s0036-46652007000500004
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibility testing of dermatophytes isolated from pediatric cases in Nigeria against five antifungals

Abstract: SUMMARYThe antifungal activities of itraconazole, ketoconazole, fluconazole, terbinafine and griseofulvin were tested by broth microdilution methods against 71 isolates of dermatophytes isolated from Nigerian children. Most drugs were very active against all the dermatophytes and the MIC 90 ranged from 0.03 to 8.0 µg/mL. This appears to be the first documented data on the antifungal susceptibility testing of isolates of dermatophytes from Nigerian children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
4
6
1
Order By: Relevance
“…Terbinafine was effective against dermatophyte isolates with a MIC range of 0.007–0.5 μg/ml. Similar findings were reported by other researchers . For T rubrum isolates, amphotericin B was more active than miconazole, itraconazole, ketoconazole, and griseofulvin ( P < 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Terbinafine was effective against dermatophyte isolates with a MIC range of 0.007–0.5 μg/ml. Similar findings were reported by other researchers . For T rubrum isolates, amphotericin B was more active than miconazole, itraconazole, ketoconazole, and griseofulvin ( P < 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…For this reason, we used agar-based dilution method that enables determining the efficacy of various antifungal drugs against various fungal genera and species. We found that the MIC ranges for dermatophytes against terbinafine was similar to those previously found by several researchers [39,33,5]. Therefore, this assay can be adapted for routine diagnosis in the laboratory and for assessment of dermatophyte resistance against antifungal drugs.…”
Section: Discussionsupporting
confidence: 87%
“…Although infections by Trichophyton are usually restricted to the superficial epidermis, these fungi may be invasive and cause a severe and disseminated infection in immune compromised patients, such as those associated with AIDS, diabetes mellitus, organ transplantation with the development of dermatophytic granulomas [33,41,44]. Thus, the identification of genetic features in Trichophyton strains resistant to antifungal agents might help considerably in the treatment and prophylaxis of dermatophytosis.…”
Section: Introductionmentioning
confidence: 99%
“…28 Susceptibility data against our 12 isolates of T. rubrum were also in agreement with other studies that point out to high MIC values for fluconazole and better response of terbinafine as an antifungal against dermatophytes. 3,22,29 …”
Section: Discussionmentioning
confidence: 99%